Laryngeal aspergillosis following high dose inhaled fluticasone therapy for asthma. Issue 9 (1st September 1999) - Fairfax, A J; David, V; Douce, G
Abstract : The case history is presented of a 75 year old man with chronic asthma who was treated with inhaled fluticasone propionate in a daily dose of 2 mg using a Diskhaler. After three years of treatment he developed progressive hoarseness. Both vocal cords were colonised by Aspergillus fumigatus which formed a white slough on the surface. Biopsy specimens showed changes suggestive of laryngeal aspergillosis with an ulcerated epithelium, fibrinopurulent debris, and colonies of fungal hyphae. A slow recovery occurred after three months of treatment with topical amphotericin and with cessation of inhaled corticosteroids. Laryngoscopy is recommended if hoarseness occurs during treatment with fluticasone.